Art and human nature XVII - Musso, Carlos G.; Enz, Paula A. (Revista del Hospital Italiano de Buenos Aires, 2014)
In his novel Demian, Hermann Hesse shows how friendship creates bonds by which human beings offer each other dialogue, understanding, help and sympathy, to get in tune with the desires, joys and sorrows of another. Because of that friendship is one of the expressions of love, and thus one of the most beautiful gifts of life
Keywords: friendship; Demian; Hesse